Coupons Versus Rebates - Lu, Qiang; Moorthy, Sridhar (Marketing Science, 2007)
This paper examines a key difference between two promotional vehicles, coupons and rebates. Whereas coupons offer deals up front, with the purchase of the product, rebates can be redeemed only after purchase. When consumers experience uncertain redemption costs, this difference translates to a difference in when uncertainty is resolved. With coupons the uncertainty is resolved before purchase; with rebates the uncertainty is resolved after purchase. As a result, we show that rebates are more efficient in surplus extraction but coupons offer more finetuned control over whom to serve. We identify the conditions under which each is optimal, and these conditions turn on the gap between “low” reservation price consumers’ valuations and their highest redemption costs. Rebates are optimal when this gap is large; coupons tend to be optimal otherwise. Risk aversity on the part of consumers reduces the attractiveness of rebates, as does the delay between rebate redemption and rebate payment, but the latter if and only if consumers are more impatient than the seller. These observations match up well with what we know about the use of these promotional vehicles in the real world.